LAYANAN KOMUNIKASI PERSUASIF: SUATU UPAYA PENINGKATKAN PERAN AKTIF PESERTA TUTON TERKATEGORI PASIF - Windrati, Nila Kusuma (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2014)
Persuasive communication model for online tutorial participants categorized passive developed to increase their active role in the activities online tutorial. The development of this model is done considering the number of participants categorized Tuton passive in every semester, one of them is Online tutorial participants for the course Introduction to Communication Studies (SKOM 4101). Though their active role in the activities online tutorial (in discussion or workmanship assignment) will contribute positively to indigo final exam for the course related. This research is research Research And Development, with the following stages : (1) conduct an inventory of the participants Tuton Communication Studies introductory course registration period 2013.1 categorized passive, (2) conduct a survey of students participating in Science Communication Tuton introductory course registration period 2013.1 categorized passive and chosen as research respondents, in order to determine the factors that cause they do not participate actively in the activities online tutorial, (3) develop a model of persuasive communication service, (4) to test a model to study respondents using the experimental method is the stage of activity pretest, treatment, posttest . The population in this study were all students participating online tutorial Introduction to Communication Studies class 01 at the time of registration are categorized passive 2013.1. Samples were taken from the overall population. The findings showed that: (1) there are 37 participants online tutorial Introduction to Communication Studies class 01 which categori passive, (2) factor is the reason for their inactivity in online tutorial activities are busy work, so they do not have the time to participate in activities online tutorial that they follow, (3) model of persuasive communication services is developed in the form of persuasive communication services electronic mail sent directly to the email address of each respondent, (4) trial results letter persuasive communication services developed shows that a change in the behavior of respondents, which they then became active in the delivery online tutorial indicated task by respondents after they acquire electronic mail that is packaged in the form of persuasive communication Model komunikasi persuasif bagi peserta tutorial online (tuton) terkategori pasif dikembangkan guna meningkatkan peran aktif mereka dalam kegiatan tuton. Pengembangan model ini dilakukan mengingat masih banyaknya peserta tuton yang terkategori pasif pada tiap semester, salah satunya adalah peserta tuton untuk matakuliah Pengantar Ilmu Komunikasi (SKOM 4101). Padahal peran aktif mereka dalam kegiatan tuton (dalam diskusi maupun pengerjaan tugas) akan berkontribusi secara positif terhadap nilai ujian akhir untuk matakuliah terkait. Penelitian ini merupakan jenis penelitian Research And Development, dengan tahapan sebagai berikut: (1) melakukan inventarisasi peserta tuton matakuliah pengantar Ilmu Komunikasi masa registrasi 2013.1 yang terkategori pasif, (2) melakukan survai kepada mahasiswa peserta tuton matakuliah Pengantar Ilmu Komunikasi masa registrasi 2013.1 yang terkategori pasif dan terpilih sebagai responden penelitian, guna mengetahui faktor-faktor yang menyebabkan mereka tidak berpartisipasi secara aktif dalam kegiatan tuton, (3) mengembangkan model layanan komunikasi persuasif, dan (4) melakukan uji coba model kepada responden penelitian dengan menggunakan metode eksperimen yaitu dengan tahapan kegiatan pretest, treatment, posttest. Populasi dalam penelitian ini adalah seluruh mahasiswa peserta tuton Pengantar Ilmu Komunikasi kelas 01 pada masa registrasi 2013.1 yang terkategori pasif. Sampel penelitian diambil secara keseluruhan dari populasi. Hasil temuan penelitian menunjukkan bahwa: (1) ada 37 peserta tuton Pengantar Ilmu Komunikasi kelas 01 yang tekategori pasif, (2) faktor yang menjadi alasan ketidakaktifan mereka dalam kegiatan tuton adalah kesibukan kerja, sehingga mereka tidak memiliki waktu untuk berperan aktif dalam kegiatan tuton yang mereka ikuti, (3) model layanan komunikasi persuasif yang dikembangkan adalah layanan komunikasi persuasif berbentuk surat elektronik yang dikirim langsung ke alamat email masing-masing responden, (4) hasil uji coba surat layanan komunikasi persuasif yang dikembangkan menunjukkan bahwa terjadi perubahan perilaku responden, yaitu mereka kemudian menjadi aktif dalam kegiatan tuton yang ditunjukkan dengan pengiriman tugas oleh responden setelah mereka memperoleh surat elektronik yang dikemas dalam bentuk komunikasi persuasif.